1996
DOI: 10.1002/1097-0045(199609)29:3<159::aid-pros2990290304>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Matrilysin Expression in the Involuting Rat Ventral Prostate

Abstract: Matrilysin (PUMP‐1) is a member of the matrix metalloproteinase (MMP) family of extracellular matrix degrading enzymes that has been found to be overexpressed in human prostate cancer. The rat ventral prostate (RVP) following castration has been used as a model for both tissue involution and apoptosis. Northern analysis and in situ hybridization were used to determine the time course and localization of matrilysin during 8 days of RVP involution. Northern analysis revealed that the 1.2 kb matrilysin mRNA was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 52 publications
4
28
1
4
Order By: Relevance
“…Moreover, the results presented in the present study perfectly matched those obtained by Powell et al (1996) using in situ hybridization for MMP-7 mRNA during involution of the rat ventral prostate. Those authors showed individual portions of the ducts or small clusters of epithelial cells expressing high levels of matrilysin, with adjacent ducts frequently negative.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the results presented in the present study perfectly matched those obtained by Powell et al (1996) using in situ hybridization for MMP-7 mRNA during involution of the rat ventral prostate. Those authors showed individual portions of the ducts or small clusters of epithelial cells expressing high levels of matrilysin, with adjacent ducts frequently negative.…”
Section: Discussionsupporting
confidence: 88%
“…Patients with ductal metaplasia arising in the setting of chronic pancreatitis have a 16-fold increase in relative risk for pancreatic ductal adenocarcinoma (PDAC) (Lowenfels et al, 2000). MMP7 is expressed in the epithelium of pre-malignant lesions in multiple glandular tissues, including breast, prostate, and intestine (Powell et al, 1996) and is thought to influence the initiation and maintenance of metaplastic events in the pancreatic epithelium (Crawford et al, 2002). We detected elevated MMP7 levels in HNF6 Δpanc animals.…”
Section: Discussionmentioning
confidence: 99%
“…8), and also their loss of activity at day 15 postcastration indicates that these activated proteases may be related to the apoptosis or prostatic involution. Activity of proteases, including cathepsin D (Helminen et al 1972;Chiang et al 1982;Tanabe et al 1982), metalloproteases (Wilson et al 1991(Wilson et al , 1995Powell et al 1996), and plasminogen activators (Rennie et al 1984;Wilson et al 1996) have been demonstrated in the castrated rat prostates and their elevated activities are believed to be involved in the prostatic involution. Among the activated proteases, Wilson et al (1991) have identified three Ca 2+ -independent proteases (35, 73-76 kDa) and another three Ca 2+ -dependent proteases (58, 63, 66 kDa) expressed in the castrated ventral prostate.…”
Section: Fig 10mentioning
confidence: 99%